A hermenêutica da arte em Hans-Georg Gadamer - Vasconcelos, Gustavo Caverzan (2013)
It is intended to present the Hans-Georg Gadamer hermeneutics of art and his philosophical defense about the possibility of knowledge of the truth in the experience of dialogue lived by anyone that contemplates an artwork. It supports that it is possible highlighting, at first, the play concepts, of festival and symbol and then, the concepts of application and experience thought by Gadamer. In addition, it shows up how can we think the artwork as a image that presents, itself, a content of truth to the viewer, scoring the internal characteristics the way of being of the reproductive arts, statutory arts and literature. This way, it is observed the fundamental sense of participation of the people involved in the play of the art, namely, the artist creator, the representative agent and the viewer to finally show how the application of each one contribute to a significant development of the art hermeneutics. In that process, it stands out the importance of the contents legacy by the historical tradition and mobility in its facticity, to think about the hermeneutics exercises in accordance with the advent of the circumstantial truth in the presentation of the artwork.